Transnational dynamics of civil war - Checkel, Jeffrey T., 1959- (Cambridge : Cambridge University Press, 2013)
"Civil wars are the dominant form of violence in the contemporary international system, yet they are anything but local affairs. This book explores the border-crossing features of such wars by bringing together insights from international relations theory, sociology and transnational politics with a rich comparative-quantitative literature. It highlights the causal mechanisms - framing, resource mobilisation, socialisation, among others - that link the international and transnational to the local, emphasising the methods required to measure them. Contributors examine specific mechanisms leading to particular outcomes in civil conflicts ranging from Chechnya, to Afghanistan, to Sudan, to Turkey. Transnational Dynamics of Civil War thus provides a significant contribution to debates motivating the broader move to mechanism-based forms of explanation, and will engage students and researchers of international relations, comparative politics and conflict processes"--
Machine generated contents note: Part I. Civil War: Mobilizing Across Borders: 1. Transnational dynamics of civil war Jeffrey T. Checkel; Part II. Transnationalized Civil War: 2. Copying and learning from outsiders? Assessing diffusion from transnational insurgents in the Chechen wars Kristin M. Bakke; 3. Mechanisms of diaspora mobilization and the transnationalization of civil war Fiona Adamson; 4. Refugee militancy in exile and upon return in Afghanistan and Rwanda Kristian Berg Harpviken and Sarah Kenyon Lischer; 5. Rebels without a cause? Transnational diffusion and the Lord's Resistance Army, 1986-2011 Hans Peter Schmitz; 6. Transnational advocacy networks, rebel groups, and demobilization of child soldiers in Sudan Stephan Hamberg; 7. Conflict diffusion via social identities: entrepreneurship and adaptation Martin Austvoll Nome and Nils B. Weidmann; Part III. Theory, Mechanisms, and the Study of Civil War: 8. Causal mechanisms and typological theories in the study of civil conflict Andrew Bennett; 9. Transnational dynamics of civil war: where do we go from here? Elisabeth Jean Wood.
Includes bibliographical references (pages 259-294) and index.
Keywords: Civil War; International relations; POLITICAL SCIENCE / International Relations / General